Comparison of the Effectiveness of Child-Centered Mindfulness Training and Art (Drawing) Therapy on Behavioral Problems and Cognitive Assessment in Children with Hearing Loss in the City of Bukan - Ahmadnezhad, Khaled; Shaker Dioulagh, Ali; Khademi, Ali (Psychological Research in Individuals with Exceptional Needs, 2025)
The aim of the present study was to compare the effectiveness of child-centered mindfulness training and art (drawing) therapy on behavioral problems and cognitive assessment in children with hearing loss in the city of Bukan. This study was applied in nature and, in terms of data collection, employed a semi-experimental field design. The research method was a quasi-experimental pretest–posttest design with a control group and a follow-up period. The study population consisted of all male and female children with hearing loss in Bukan County. A total of 45 children were assigned to three groups: two intervention groups with 15 participants each and one control group with 15 participants. The research instruments included two educational intervention packages and two questionnaires. The child-centered mindfulness training package was based on the program developed by Bordick (2017), and the art therapy training package was based on Martin’s program (2009). In addition, the Revised Behavior Problem Checklist for Children and Adolescents (RBPC) developed by Quay and Peterson, and the Children’s Cognitive Assessment Questionnaire (CCAQ) developed by Zater and Chassin, were used in this study. Based on the findings, no statistically significant difference was observed between the effectiveness of the two interventions in reducing children’s cognitive assessment scores (p < .05). On the other hand, neither intervention had a statistically significant effect on reducing behavioral problems in children (p > .05). It can be concluded that both therapeutic approaches may be used as effective interventions for improving certain psychological and cognitive aspects of children with hearing loss; however, alternative or complementary approaches may be required to address behavioral problems.